IMPLEMENTASI METODE K-NEAREST NEIGHBOUR (K_NN) UNTUK MENDUGA SALINITAS AIR LAUT - yuri efenie; Miftahul Walid (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2020)
In this research, trying to predict the salinity of sea water using the K-Nearest Neighbor method, this method serves to clarify the input data using the distance measurement method with training data, the variable used in this study is the value of the location of coordinates (latitude and longitude) and the output is in the form of salinity, the case study in this study is the southern waters of Sumenep, the system has been able to make an estimate but with an error rate of 1.00 so that there is a need for re-analysis because the data used is only small, the need for additional data so that the results will be more optimal, it is also necessary to experiment with changing methods or simplifying rules or by adding input variables in the system that have been created so that it produces better accuracy values, because the existing system still requires a long time in estimating.